Needs Analysis in Technical Vocational Education and Training (TVET) Programs for Sustainable Development of Women in Cambodian Hair and Beauty Industry - Bang, Yonghwan; Park, Taejung (Journal of Technical Education and Training, 2021)
This study explored the status and needs of Cambodia Technical Vocational Education Training (TVET) for the hair and beauty industry to develop Cambodia’s first online TVET diploma curriculum for hair and beauty localize from the curricula of the Korean online (cyber or digital) universities specialized in hair and beauty industry. The study conducted a comprehensive situational analysis using qualitative approach through focus group interviewing government personnel, industry, TVET institution and used a descriptive survey to potential 176 students: 116 hair shop owners and 60 staff. The findings confirmed that stakeholders from government, industry, and TVET institutions expressed high need to introduce an innovative online hybrid model of TVET diploma program for the development of Cambodia hair and beauty industry as well as potential students from the industry. In conclusion, the results suggest that adopting a hybrid blended learning approach in TVET should be encouraged under the current Covid-19 pandemic. The study recommended further studies to evaluate its effectiveness and impact of this newly designed program with various perspective from the individual level, institutional level, and hair and beauty TVET sector in Cambodia.